Evidence for Adaptation to the Tibetan Plateau Inferred from Tibetan Loach Transcriptomes. (9th October 2015) - Wang, Ying; Yang, Liandong; Zhou, Kun; Zhang, Yanping; Song, Zhaobin; He, Shunping
Abstract: Triplophysa fishes are the primary component of the fish fauna on the Tibetan Plateau and are well adapted to the high-altitude environment. Despite the importance of Triplophysa fishes on the plateau, the genetic mechanisms of the adaptations of these fishes to this high-altitude environment remain poorly understood. In this study, we generated the transcriptome sequences for three Triplophysa fishes, that is, Triplophysa siluroides, Triplophysa scleroptera, and Triplophysa dalaica, and used these and the previously available transcriptome and genome sequences from fishes living at low altitudes to identify potential genetic mechanisms for the high-altitude adaptations in Triplophysa fishes. An analysis of 2, 269 orthologous genes among cave fish ( Astyanax mexicanus ), zebrafish ( Danio rerio ), large-scale loach ( Paramisgurnus dabryanus ), and Triplophysa fishes revealed that each of the terminal branches of the Triplophysa fishes had a significantly higher ratio of nonsynonymous to synonymous substitutions than that of the branches of the fishes from low altitudes, which provided consistent evidence for genome-wide rapid evolution in the Triplophysa genus. Many of the GO (Gene Ontology) categories associated with energy metabolism and hypoxia response exhibited accelerated evolution in the Triplophysa fishes compared with the large-scale loach. The genes that exhibited signs of positive selection and rapid evolution in the Triplophysa fishes were also significantly enriched in energy metabolism and hypoxia response categories. Our analysis identified widespread Triplophysa -specific nonsynonymous mutations in the fast evolving genes and positively selected genes. Moreover, we detected significant evidence of positive selection in the HIF (hypoxia-inducible factor)-1A and HIF-2B genes in Triplophysa fishes and found that the Triplophysa -specific nonsynonymous mutations in the HIF-1A and HIF-2B genes were associated with functional changes. Overall, our study provides new insights into the adaptations and evolution of fishes in the high-altitude environment of the Tibetan Plateau and complements previous findings on the adaptations of mammals and birds to high altitudes.